2020
DOI: 10.3390/geosciences10110430
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Susceptibility Mapping Using Statistical Methods along the Asian Highway, Bhutan

Abstract: In areas prone to frequent landslides, the use of landslide susceptibility maps can greatly aid in the decision-making process of the socio-economic development plans of the area. Landslide susceptibility maps are generally developed using statistical methods and geographic information systems. In the present study, landslide susceptibility along road corridors was considered, since the anthropogenic impacts along a road in a mountainous country remain uniform and are mainly due to road construction. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…The more the distance from the road increases, the more the probability of a landslide decreases. This negative trend was observed by other authors worldwide [62][63][64][65], highlighting the importance of anthropogenic impact on slope stability. Additionally, other authors [26,66] reported that the landslide susceptibility gradually increases up to a proximity zone of 200 m from a road network.…”
Section: Correlation Analysissupporting
confidence: 68%
“…The more the distance from the road increases, the more the probability of a landslide decreases. This negative trend was observed by other authors worldwide [62][63][64][65], highlighting the importance of anthropogenic impact on slope stability. Additionally, other authors [26,66] reported that the landslide susceptibility gradually increases up to a proximity zone of 200 m from a road network.…”
Section: Correlation Analysissupporting
confidence: 68%
“…Moving forward, it is crucial to enhance and refine GIS-based techniques for landslide risk assessment (Nseka et al, 2021). Additionally, there is a need for continuous monitoring and updating of spatial data to ensure the accuracy and reliability of landslide susceptibility maps (Pasang and Kubíček, 2020). However, it is essential to integrate other factors, such as land use changes, climate change, and human activities, into landslide risk assessment models.…”
Section: Future Perspectives For Landslide Risk Managementmentioning
confidence: 99%
“…While often natural in origin, many landslides are triggered and aggravated by human-induced factors. Destruction of infrastructure, disruption of transportation and telecommunications networks, washing away of fertile soil, and fatalities are some serious risks associated with landslides in Bhutan (Pasang and Kubíček 2020). To mitigate the landslide consequences, disaster management is explicitly recognized as a part of sustainable development goals.…”
Section: Introductionmentioning
confidence: 99%